DINAMIKA AGRIBISNIS TEMBAKAU DUNIA DAN IMPLIKASINYA BAGI INDONESIA (Forum Penelitian Agro Ekonomi, 2017)
Tobacco is one of the world’s important commodities in trading. The main products of tobacco are tobacco leaf and cigarette. Since 2000’s world agribusiness of tobacco tended to decrease after experiencing a high growth in few decades. This was indicated by the decreasing growth of harvested area, production and consumption of tobacco leaves and cigarettes. This situation was primarily affected by the increasing public pressure against tobacco, mainly in developed countries, due to health and environmental aspects. Developed countries responded the dynamics by the application of a policy to restrict tobacco in their land and move the production to developing countries. Production of tobacco decreased faster than its consumption causing larger gaps between supply and demand of tobacco leaf. On the other hand, the market of tobacco supply and demand grow along with the growth of population triggering the increase of tobacco leaf world price. The potential market would be available in developing countries such as Indonesia, in short and intermediate terms. Indonesia is a potential market for cigarette. This fact is in line with the number of population and its smoking culture. Large cigarette companies and multi national corporations take huge advantages from such promising market in Indonesia. The existence of both could raise investment instead of disadvantaged public and government of Indonesia by causing unexpected negative impacts and social costs. Indonesia should redirect industrial products of tobacco from domestic to export markets. The export potential could be empowered by: (a) strengthening priority on the existing marketable products (b) prioritize the competitiveness of  the Na Oogst (cigars), and (c) shift production of cigarettes from the unfiltered and filtered to the light and ultra light cigarettes and promote the export markets. In a long term, it is necessary to anticipate the decrease of tobacco/cigarettes’ demand by introducing alternative high value crops to substitute tobacco. The substitution effort must be supported by all stakeholders at whom the decision makers could guarantee the substitute crops market and price.